Land-Use Shifting from Settlement into Commercial in Caturtunggal, Sleman - Aulia, Fauzia Ghitha; Haryanto, Ragil; Pradoto, Wisnu (JEJAK: Jurnal Ekonomi dan Kebijakan, 2020)
Caturtunggal area is a residential area that is growing rapidly, especially in commercial activities. Current commercial activities have expanded into residential areas. Caturtunggal is one of the regions with an educational function and has become a new center of growth in Sleman Regency with the presence of Gadjah Mada University (UGM) and Yogyakarta State University (UNY). The development of commercial activities in the region to facilitate trade activities and services between people in need such as students (demand) and people who sell services (supply) that can create workers in urban areas so that they can contribute to the regional economy and Gross Regional Domestic Product (GRDP). The purpose of this study is to determine the development of changes in spatial use from settlements to commercial activities in the Education Area and formulate the factors that cause a shift in the use of space in the region. The method used in this research is quantitative methods and analysis techniques using spatial analysis, descriptive statistical analysis and factor analysis. The subject of this research is small-medium commercial activity in the Caturtunggal region. The results of this study were found as a phenomenon of 70% shift in the use of space to be commercially caused by 5 factors, namely economic factors, the existence of educational areas, locations, market preferences, and access.